Characteristics of Evaluation in Vocational Training from a Competency-Based Approach - Nieto Ortiz, Jorge; Millán Gutiérrez, Mª Ángeles; Lizcano Casas, David; Roa González, Julián (Avances en Supervisión Educativa, 2023)
The evaluation in Vocational Training is usually developed from the competences and it is key to stimulate the level and depth of learning. In this regard, it seeks to know the characteristics of competency assessment addressed in the scientific literature, with the purpose of contributing to the new assessment models that arise in an environment of change for Professional Training. A bibliographical investigation of articles has been proposed using the CIRC classification as a filter. Sources have been investigated that will collect the latest trends regarding the evaluation in the last twenty-one years. The most significant characteristics of the evaluation by competencies have been obtained from the formative approaches based on the competencies. Some of the problems that hinder the implementation of evaluative models for the evaluation of competences such as the measure have been shown. Finally, future lines of research aimed at formulating new evaluative models are proposed.
Keywords: vocational training; formative evaluation; evaluation criterion; continuous assessment